Exploring the solar system - Bond, Peter 1948- (Wiley-Blackwell, 2020)
"For millennia, people have studied the heavens and wondered about the nature and origins of the Sun, Moon and planets. Indeed, Solar System studies dominated the field of astronomy until the introduction of powerful telescopes and advanced instruments in the 19th century. In the last 50 years, spacecraft have flown past or orbited all of the major planets and two dwarf planets, landed on the Moon, Mars, Titan, a comet and an asteroid. They have also brought back samples of Moon rock, comet and asteroid dust, as well as the solar wind. This era of robotic and human exploration has revolutionized scientists' knowledge of our corner of the Galaxy, and further astounding revelations are expected in the decades to come"--Provided by publisher.